2019
DOI: 10.3390/s19122749
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized QoS Prediction Method for Web Services via Blockchain-Based Matrix Factorization

Abstract: Personalized quality of service (QoS) prediction plays an important role in helping users build high-quality service-oriented systems. To obtain accurate prediction results, many approaches have been investigated in recent years. However, these approaches do not fully address untrustworthy QoS values submitted by unreliable users, leading to inaccurate predictions. To address this issue, inspired by blockchain with distributed ledger technology, distributed consensus mechanisms, encryption algorithms, etc., we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The top row is the result of the real observation, and the bottom row is the result of our algorithm. By comparing and analyzing the data from the four groups (see Fig 3), it can be observed that deviation of the parameters is in the acceptable range [31]. In our experiment, we carefully compared all the game parameters of different teams in the 2016 and 2017 NBA Finals.…”
Section: Casestudymentioning
confidence: 99%
“…The top row is the result of the real observation, and the bottom row is the result of our algorithm. By comparing and analyzing the data from the four groups (see Fig 3), it can be observed that deviation of the parameters is in the acceptable range [31]. In our experiment, we carefully compared all the game parameters of different teams in the 2016 and 2017 NBA Finals.…”
Section: Casestudymentioning
confidence: 99%
“…Combining credits of privacy-preservation of blockchain, Li et al [65] proposed a blockchain-based QoS-aware web services recommendation framework. At the same time, Cai et al [64] proposed a personalized blockchain-based prediction approach. Both of them are the variants of matrix factorization.…”
Section: Services Recommendation Based On Blockchainmentioning
confidence: 99%
“…In recent years, the network environment has become increasingly complex. Traffic data have exploded and mass infrastructure based on internet of things (IoT) technology and complex networks has had a significant impact on society and the economy [ 1 3 ]. Due to the increase in Internet services, network abnormalities including malicious attacks and poor quality of network services have become more diversified and substantially affecting the operation of web services and causing social and economic losses [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%